Mediatised Home: Using Semiotic Repertoires in Online Workplace Communications - Kozhemyakin, Evgeny A. (Communication Today, 2021)
Since 2020, people have faced the challenge of constructing new visual modes of online workplace meetings, because we had to use our home for working communications purposes and as a new medium. Mediatisation of home involves redefining semiotic resources and communicational norms concerning the appearance of participants, the background, the use of camera and microphone. The results of the poll demonstrate that this redefining has two aspects: 1) the use of semiotic repertoire to transmit meaningful information about the self and own positions, attitudes, and roles in the communication; and 2) normalisation of own and others’ actions during online meetings from home. The results of the survey contribute to awareness of how the issue of private and working/corporate places is being debated. The author claims that technical aspects of online meetings are at the beginning of their ethical reconstruction, which would provide online workplace communications with new traditions and rules of use of camera and microphone as meaningful parts of the semiotic repertoire.